THE REVIEW OF THE SYMBOLIC UNIVERSE OF THE PHYSICAL EDUCATION LEGITIMIZATION IN THE PASSAGE FROM SOLID MODERNITY TO LIQUID MODERNITY (Fiep Bulletin - online, 2015)
In this article we discuss the symbolic universe of the Physical Education legitimization as a curricular component from the hypothesis that, when constructed in the context of the modernity denominated solid by Bauman (2001), it presents clear signs of exhaustion if we consider the current context of liquid modernity according to the denomination of the same author. We have tried to demonstrate, based on a broad documental foundation, how the symbolic universe of the Physical Education legitimization was linked to the modernity guiding principles in its solid phase and identify which challenges lay ahead the construction of a legitimization symbolic universe in the epistemological and social-cultural transition picture which characterizes the passage to modernity in its liquid phase.
Keywords: Physical Education; modernity; symbolic universe; legitimacy.